INTIMATE RELATIONSHIP IN TA’ARUF COUPLE - Marlia Rahma Diani; Sri Widowati Herieningsih; Turnomo Rahardjo; Agus Naryoso (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2015)
Marriage is something coveted in every relation. There are some ways of introducing to acouple before the wedding. Ta’aruf couples through their introducing and also developing oftheir relationship in a very short. So they didn’t know each other in a specific things.Communication between ta’aruf couples also must go by a mediator. It causes for thedistortions messages in their communication. Besides information about the couple obtainedfrom the process of ta’aruf is also limited because of the intercommunication limits that mustbe obeyed restrictions in accordance with islamic syariah.The purpose of this research is to find the experience of the ta’aruf couples in undergothe process at the communication time and knowing that occur in pairs of closeness inrelationships or intimate relationship. The used theories are Penetration Social Theory byIrwin Altman Damask and Taylor and the Dialectics Relational Theory by Baxter andMontgomery. To describe in detail to the development of intimate relationship in the ta’arufcouples. This research is using qualitative methodology with the approach phenomenology.Subject in this research is the newly married ta’aruf couples, with two or three months ofmarried using ta’aruf process.Based on the results, ta’aruf became a means to know each other and get informationfrom each other to minimize uncertainty information between one another. The ta’arufcouples began to minimize the uncertainly general information of themselves by exchangetheir curriculum vitae who mediated by a mediator.Trust, self disclosure, and responsibilities are becoming a key in relations developingfor a familiar intercourse between ta’aruf couples. In facing a conflict, a ta’aruf couple like todiscussing with a mediator to the conflict that appears. So it would not be a failed factor inta’aruf process.